(3LQGFe GdEJLGQ HGdCWaGd (B/ s - (3SYjO eMQhS CMeO CHhGdYdGs; (3WGQb CMeO aJMi SQhQ s; (3GdbGgQIs ((3GdbGgQIs (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2019)
(3JfGhdJ GdOQGSI LQGFe GdGJLGQ HGdCWaGd(B: (3h Pdc HGdJYQV dMeGjI GdCWaGd ef NWQ GdGJLGQ Hge(B: (3h GdJi JYO fhYkG ef GdYHhOjI GdMOjKI(B: (3GdJi CYjO EfJGLgG(B: (3h XgQJ HbhI ai fgGjGJ GdbQf GdYTQjf efJLg CfeGWkG LOjOI ef GdGJLGQ HGdHTQ(B: (3h eY YhOI GdYHhOjI HgPg GdbhI GdeJeKdI ai GdGJLGQ HGdHTQ(B: (3h HGdCNU GdCWaGd CUHMJ JcGO Jchf eTcdI YGdejI(B: (3JfTQ ai cKjQ ef Ohd GdYGde(B: (3HUhQI JgOO CefgG GdEfSGfi(B: (3h GdGLJeGYi h Gdbhei(B: (3h dbO HOC GdYGde HYO cKjQkG ef GdJLGgd h GddGeHGdGI jSJjbX Ydi MbjbI JJYdb HTcd MOjK ef CTcGd GdQb(B: (3h GUHM GdfGS h hSGFd GdCYdGe jOQchf HCf HTQkG jaJQShf HTkQG BNQjf ef CLd GdeGd(B: (3h gh eG OaY GdCee GdeJMOI Edi Cf JYdf Cf gPG GdfTGW GdLOjO ef GdYHhOjI GdPi jfJL ddYGde CQOC CfhGY GdGJLGQ EdG h gh GdGJLGQ HGdHTQ(B: (3h jCJi HGdeQJHI GdKGdKI HYO GdGJLGQ HGdSdGM h GdeNOQGJ(B. (3h dbO JYQV GdHGMK ai GdbSe GdChd ef GdOQGSI dHjGf JLQje GdGJLGQ HGdCWaGd HOGjI ef GdebUhO HLQjeI GdGJLGQ HGdCWaGd Ch HGdHTQ YehekG h Pdc ai Gdabg GdESdGei(B: (3h Pdc dCf GdESdGe TQY GdYJb(B: (3h de jfTC GdQb hPdc dCf GdQb cGf oYQa eJLPQ YfO GdYQH h dbO JUOi dg GdESdGe h MGQHg MJi bVi Ydjg(B: (3deG ajg ef GeJgGf dcQGeI GdEfSGf h Pdc dCf GdEfSGf djS eMdkG ddJYGed Ch GdGJLGQ Hg(B: (3h dbO bGd Gddg JHGQc h JYGdi(B: (3nhndnbrO ncnqQrenfG nHpfi BnOne(B. (3h cPG GdebUhO HJdc GdLQjeI ai GdbGfhf GdhVYi h eQhQkG HCQcGfgG h GdYbhHGJ GdebQQI dgG ai Gdabg GdESdGei h GdbGfhf GdhVYi ai GdbhGfjf CQbGe (B126 (3dSfI (B2008 (3bGfhf GdWad GdLOjO(B: (3h GdbGfhf Qbe (B64 (3dSfI (B2010 (3HTCf ecGaMI GdGJLGQ HGdHTQ eeG jDcO Cf eUQ bO ChdJ GgJeGekG HXGgQI GdGJLGQ HGdHTQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2019s
Keywords: (3GdGJLGQ HGdGWaGds; (3CQcGf GdEJLGQ HGdCWaGd s; (3GdEJLGQ HGdCWaGd ai Gdabg GdESdGeis; (3GdEJLGQ HGdCWaGd ai GdbGfhf GdhVYis; (3YbhHI LQGFe GdGJLGQ HGdGWaGds; (3GdYeGdI GdbSQjI ddGWaGd(B-(3GWaGd GdThGQYs; (3ehGLgg LQGFe GdGJLGQ HGdGWaGd Ydj GdeSJhi GdGbdjejs; (3ehGLgg LQGFe GdGJLGQ HGdGWaGd Ydj GdeSJhi GdOhdjs; (3RhGL GdbGUQGJ aj GWGQ GdGJLGQ HGdGWaGds; (3RhGL GdbGUQGJ aj GWGQ GdGJLGQ HGdGWaGds; (3GdeSGgeI GdLfGFjI aj LQGFe GdGJLGQ HGdGWaGds; (3GSJZdGd GdGWaGd aj GdGfJQfJ hGdGSJZdGd GdLfSj dges; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs